Next Generation Sequencing in the Clinic: a Patterns of Care Study in a Retrospective Cohort of Subjects Referred to a Genetic Medicine Clinic for Suspected Lynch Syndrome. Issue 3 (5th December 2015) - Gallego, Carlos J.; Perez, Matthew L.; Burt, Amber; Amendola, Laura M.; Shirts, Brian H.; Pritchard, Colin C.; Hisama, Fuki M.; Bennett, Robin L.; Veenstra, David L.; Jarvik, Gail P.
Abstract: Next generation sequencing (NGS) gene panels are increasingly used in medical genetics clinics for the evaluation of common inherited cancer syndromes, but the clinical efficacy of these tests, and the factors driving clinical providers to order them are unclear. We conducted a patterns‐of‐care study to compare patients evaluated with NGS gene panels with a reference group. We abstracted demographic, socioeconomic, and clinical information in a retrospective cohort of patients referred to a large medical genetics clinic for evaluation of inherited colorectal cancer and polyposis syndromes. Patients tested with NGS gene panels were more likely to be insured compared to the reference group (85.3 % vs. 69.2 %, p = 0.0068), less likely to have prior tumor tissue testing (29.4 % vs. 54.3 %, p = 0.0004), and less likely to have an abnormal tumor tissue test result (46.7 % vs. 74.5 %, p = 0.01). No significant differences were found between groups in age, gender, race, employment status, personal history of colorectal cancer, or proportion of patients fulfilling Lynch syndrome clinical criteria. Patients with NGS testing were less likely to have a pathogenic/likely pathogenic variant detected (13.7 % vs. 31.9 %, p = 0.002). Patients referred for NGS testing to evaluate inherited colorectal cancer/polyposis risk appear to undergo tumor tissue testing less frequently than non‐NGS testing patients. Further studies are needed to assess the most effective and cost‐effective approach to genomic diagnosis in this patient population.